2015
DOI: 10.7150/thno.11387
|View full text |Cite
|
Sign up to set email alerts
|

Graphene as Cancer Theranostic Tool: Progress and Future Challenges

Abstract: Nowadays cancer remains one of the main causes of death in the world. Current diagnostic techniques need to be improved to provide earlier diagnosis and treatment. Traditional therapy approaches to cancer are limited by lack of specificity and systemic toxicity. In this scenario nanomaterials could be good allies to give more specific cancer treatment effectively reducing undesired side effects and giving at the same time accurate diagnosis and successful therapy. In this context, thanks to its unique physical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
140
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 247 publications
(141 citation statements)
references
References 133 publications
(339 reference statements)
1
140
0
Order By: Relevance
“…The sp 2 -hybridized carbon atoms in a honeycombed network provide graphene with a large surface area (2630 m 2 g −1 ), outstanding thermal conductivity (~5000 Wm K −1 ), high mechanical strength (~1.1 TPa), and elasticity [8]. These properties of graphene have provided a stepping-stone for the development of nanocarriers for drug and gene delivery, biosensors, cell imaging, and phototherapy of cancer [9][10][11][12][13][14][15][16][17][18][19][20]. Doxorubicin loaded onto PEG-NGO conjugate is a primary example that utilizes the delocalized surface π-electrons in graphene to enhance the solubility of poorly soluble drugs [6].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The sp 2 -hybridized carbon atoms in a honeycombed network provide graphene with a large surface area (2630 m 2 g −1 ), outstanding thermal conductivity (~5000 Wm K −1 ), high mechanical strength (~1.1 TPa), and elasticity [8]. These properties of graphene have provided a stepping-stone for the development of nanocarriers for drug and gene delivery, biosensors, cell imaging, and phototherapy of cancer [9][10][11][12][13][14][15][16][17][18][19][20]. Doxorubicin loaded onto PEG-NGO conjugate is a primary example that utilizes the delocalized surface π-electrons in graphene to enhance the solubility of poorly soluble drugs [6].…”
mentioning
confidence: 99%
“…A literature review shows that 73 % of the research works have been associated to drug and gene delivery applications; 32 % on photothermal therapy, 31 % on imaging, 10 % on photodynamic therapy, and 27 % of the studies on the theranostic applications [16]. Considering that in vivo delivery issue has been continuously emphasized as a main bottleneck in a drug development area, numerous trials using nanomaterials such as graphene could contribute to overcoming the in vivo targeted delivery issue.…”
mentioning
confidence: 99%
“…Reaction between the carboxylic groups of GO and hydroxyl groups of TiO 2 forms the basis for the creation of the GOT (14). For these reasons, GO NPs have been proposed for treatment of cancer (5). As an evidence, Fiorillo et al revealed that GO NPs could eradicate cancer stem cells, offering them as a new therapeutic strategy of cancer (22).…”
mentioning
confidence: 99%
“…It is believed that this novel therapeutic modality has no harmful side-effects of chemotherapy and radiotherapy, including multi-drug resistance and effect on normal cells (4). Different types of PSs, such as hypericin, Protophorphyrin IX (PPIX), and benzoporphyrin derivatives, showed promising therapeutic effects in skin cancer and melanoma (5). However, these kinds of PSs have several limitations, including low solubility, instability, and short half-life in the tissue, suggesting a need for finding new potent PS (6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation